Modeling fire‐related smoke inhalation injury using the human lung‐on‐a‐chip and organoid platform: Pathogenesis insights and therapeutic evaluation - Junmin Li; Dezhong Zhang; Yan Meng; Yongqing Chang; Wenbo Wei; Peng Wu; Lin Peng; Wei Chang; Wei Wang; Jie Huang; Jingjing Fang; Keming Zhu; et al. (View)
Abstract Fire‐related smoke inhalation‐induced acute lung injury (SI‐ALI) is a prevalent condition in modern fires, characterized by high mortality and a lack of targeted therapeutic options. Previous research has been hindered by instability in smoke generation and modeling methods, limiting the investigation of SI‐ALI mechanisms. This study, for the first time, utilized organ‐on‐a‐chip and organoid technologies, optimizing chip design and precisely controlling smoke generation from non‐metallic materials to establish a human‐relevant, physiologically accurate model of fire‐related SI‐ALI. The results demonstrate that this model effectively simulates the alveolar‒capillary barrier and replicates key pathological features of lung injury, including oxidative stress, apoptosis, immune cell adhesion, inflammatory responses, capillary leakage, and mitochondrial damage. Injury responses of endothelial and epithelial cells to smoke exposure were thoroughly assessed at the organ level. Integrating proteomics and molecular biology techniques, along with comparisons to animal models, identified disease‐specific pathways related to the spliceosome and carbon metabolism, as well as pathogenic molecules such as catechol‐O‐methyltransferase (COMT) and nitrilase 1 (NIT1). Furthermore, molecular docking of COMT revealed potential therapeutic candidates from the FDA‐approved drug library, including Ractopamine HCl and Bimatoprost. The efficacy of intravenous vitamin C combined with nebulized budesonide was validated on the chip model, establishing a foundation for clinical applications. This study provides a robust model for investigating fire‐related SI‐ALI and offers novel insights into underlying mechanisms and therapeutic development.